A Preliminary Evaluation of Transdiagnostic Group Metacognitive Therapy in a Mixed Psychological Disorder Sample - Callesen, Pia; Capobianco, Lora; Heal, Calvin; Juul, Carsten; Find Nielsen, Sisse; Wells, Adrian (Frontiers in Psychology, 2019)
Objective: Comorbidity is common among anxiety and depression. Transdiagnostic treatment approaches have been developed to optimize treatment and offer a more unified approach suitable for individuals with comorbidities. Metacognitive therapy (MCT) is a transdiagnostic therapy for psychological disorder and is based on the metacognitive model. The present study is a service evaluation of the outcomes associated with group MCT delivered to unselected patients at a Danish outpatient clinic. Methods: A total of 131 self-diagnosed patients received 6 sessions of group MCT. Symptoms of anxiety and depression were measured by the Hospital Anxiety and Depression scale (HADS) and metacognition was assessed using the Cognitive Attentional Syndrome-1 (CAS-1). Participants were assessed at pre-treatment, post-treatment, and at 6 months follow-up as per usual clinic protocol. Linear mixed-effects regressions were used to assess the transdiagnostic effects of group MCT. Treatment effect sizes are reported for subgroups based on participant’s reason for seeking treatment (anxiety, depression, or comorbid). Effect sizes were not conducted for the depression subgroup given the limited number of participants. Clinically significant change is reported for all subgroups. Results: Group MCT was associated with large effect sizes for symptoms of anxiety and depression for patients seeking treatment for anxiety (d = 1.68), or comorbid (1.82). In addition, 66.7% of patients were classified as recovered at post-treatment, and 12.9% were classified as improved. These results were largely maintained at 6-month follow-up. Conclusion: These preliminary findings support the continued use of group MCT in the current outpatient clinic and suggest that it may be an efficacious and cost-effective treatment when delivered in “transdiagnostic” groups.